The Follow UpVillage Examination Report (Case StudyOn Villagein Western Sumbawa) - ,, Hapid; Herwanti, Titiek; Husnan, Hamdani (International Journal of Scientific Research and Management (IJSRM), 2018)
This study aimed to analyze the inspection reports Village in West Sumbawa qualitative method with case study approach. The phenomenon of this study are based on the results of annual monitoring by the monitoring unit of West Sumbawa District Inspectorate underlining the fact that the completion of the follow-up is still in progress and has not been acted upon. The study found a lack of good communication at the management level of the work unit Village in West Sumbawa regency and still lacks the human resources that have educational competence equivalent to its responsibilities, so that the completion of the follow-up by the work unit Village is not achieved with the maximum and the follow-up is still not followed up by the Village. For repairs to the front, in general, work units Villagers led by the Village head must have the commitment and the efforts of the completion of the follow-up so that they can communicate better and work units, especially the head of the Village with financial managers Village should involve all components within the organization to establish a pattern of relationships in the settlement of the follow-up tasks.